Final height in elite male artistic gymnasts - Georgopoulos, N. A.; Theodoropoulou, A.; Roupas, N. D.; Armeni, A. K.; Koukkou, E.; Leglise, M.; Markou, K. B. (Journal of Pediatric Endocrinology and Metabolism, 2012)
Elite male artistic gymnasts (AG) are exposed to high levels of physical and psychological stress during adolescence and experience a significant late maturation in both linear growth and pubertal development. The aim of the present study was to determine the impact of intensive physical training on the adult final height in elite male AG.